(3QMdI GdMjei Edi CQV GdMHTIs - (3GdMSf Hf CMeO GdMjej GdTHGej, GdbGVj TQa GdOjfs ((3CMeO Hf YHO Gddg Hf jMji Hf Ydi GdgGOi GdgGOhi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CJGfG ef GdEjeGf hGdJbhi hCeQfi ef dGjSYfi eNGdaJg Cf CUa dg eG jfHZi ePGcQJg GdOjGQ GdMHTjI s
(3BNQgG (B:s
(3hdeG hUdfG HfOQ GddLHI hCSQYJ HQaY GdNHQ Zdi ehdGfG CejQ GdeDefjf hcGf hUhdfG Edjg QGHY TgQ HjY GdChd hgGgfG jfJgi eG ChQOfGg hGdMeO ddg s
(3GdQMdI HWdH ef CejQ GdeDefjf GdeJhcd Ydi Gddg ESeGYjd Hf GdbGSe Edi SdWGf GdMHTI cJHJ Hbde ajg VHW heged GdfbW CMjGfkGs
(3HBNQgG CfgG QhLYJ hGfJgJ JJHYkG bUGUI ai TgQ TYHGf SfI (B1072(3g`J HChdgG Jedc SfI (B1301 (3hHgG fXGe GdJYbjHI hHg HYV WeSs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B529 s
Keywords: (3GdJGQjNs